Fabrication of Non-enzymatic Electrochemical Glucose Sensor Based on Nano-copper Oxide Micro Hollow-spheres - Haghparas, Zahra; Kordrostami, Zoheir; Sorouri, Mohsen; Rajabzadeh, Maryam; Khalifeh, Reza (Biotechnology and bioprocess engineering, 2020)
In the present study, an electrochemical glucose biosensor has been developed based on nano-copper oxide micro hollow spheres. The nano-copper oxide micro hollow spheres were synthesized via hydrothermal method using pluronic F-127 as a surfactant. For structural characterization of CuO hollow sphere structures, the scanning electron microscopy and X-ray diffraction spectroscopy were applied. The performance parameters of the sensor were improved by optimizing the modification process. The electrochemical characteristics of the proposed glucose biosensor were investigated by using cyclic voltammetry and chronoamperometry techniques in both 0.1 M and 1 M NaOH solutions. The results revealed that the proposed electrode has a wide dynamic range from 1 µM to 11.50 mM for glucose detection at 0.1 M NaOH solution which covers two linear ranges from 1 µM to 3 mM and from 3 mM to 11.50 mM. The sensitivities of the two linear ranges were obtained as 25.0 ± 0.8 µA·mM −1 ·cm −2 and 13.6 ±0.3 µA·mM −1 ·cm −2 , respectively. An extremely wide linear range from 1 µM to 16 mM with a sensitivity of 35.2 ± 0.4 µA·mM −1 cm −2 was achieved for the 1 M NaOH solution. The sensor achieved a 1 µM practical lowest limit of detection which is an excellent low limit of detection at both NaOH concentrations compared to some important previously reported works. In addition, the good tolerance toward the interfering species and the satisfactory behavior in real sample analysis verified the promising performance of the proposed sensor.